(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Bitcoin uses peer-to-peer technology to operate with no central authority or banks managing transactions and the issuing of bitcoins is carried out collectively by the network. Bitcoin is open-source its design is public, nobody owns or controls Bitcoin and everyone can take part. Through many of its unique properties, Bitcoin allows exciting uses that could not be covered by any previous payment system. Confusion reigns in India’s crypto currency ecosystem. Shri Narendra Modi government and India’s central bank have made it amply clear they aren’t comfortable with virtual currencies. The recent spike in bitcoin’s value, which attracted hordes of investors, has only made the government more vociferous in its criticism. However, these announcements don’t make these virtual currencies, or trading in them, against the law. So, their status is in a curious limbo—they’re neither legal nor illegal in India. This Per focus on the concept of Bitcoin and its legality status in India as well as in different countries,